2007
DOI: 10.5194/acpd-7-6143-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate impact of supersonic air traffic: an approach to optimize a potential future supersonic fleet – results from the EU-project SCENIC

Abstract: Abstract. The demand for intercontinental transportation is increasing and people are requesting short travel times, which supersonic air transportation would enable. However, besides noise and sonic boom issues, which we are not referring to in this investigation, emissions from supersonic aircraft are known to alter the atmospheric composition, in particular the ozone layer, and hence affect climate significantly more than subsonic aircraft. Here, we suggest a metric to quantitatively assess different option… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 38 publications
7
38
0
Order By: Relevance
“…Efficacies for a variety of climate agents are taken from Ponater et al (2005Ponater et al ( , 2006. The climate sensitivities used in this study are identical to those in Grewe et al (2007) (their Table 7). …”
Section: Contrail Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Efficacies for a variety of climate agents are taken from Ponater et al (2005Ponater et al ( , 2006. The climate sensitivities used in this study are identical to those in Grewe et al (2007) (their Table 7). …”
Section: Contrail Coveragementioning
confidence: 99%
“…2.4.1) depending on the regarded 3-D emissions. For the lifetime of a stratospheric perturbation an uncertainty range of ±40% is regarded following Grewe et al (2007), whereas for the troposphere only ±20% are taken into account, since model uncertainties in e.g. simulating tropospheric ozone lifetimes agree within this range (Stevenson et al, 2006).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…The different SCENIC air traffic datasets are discussed in detail in Rogers et al (2007) 1 . Here we give a short summary of the main characteristics of the subsonic (S1 and S4) and mixed fleet scenarios (S2 and S5) for the years 2025 and 2050 (Table 1).…”
Section: Air Traffic Inventoriesmentioning
confidence: 99%
“…Ross et al [2010] demonstrated the significant potential rockets have to alter regional RF as well as the global circulation, should certain types of space transportation grow as planned. In this context, it is perplexing that detailed models of supersonic transport emissions continue to appear in the literature [e.g., Grewe et al, 2007] when such vehicles are not likely to appear soon whereas space transportation is a growing actuality.…”
Section: Introductionmentioning
confidence: 99%